MODEL REGRESI COX PROPORTIONAL HAZARD DENGAN PENDEKATAN DISTRIBUSI POISSON PADA LAJU SURVIVAL PASIEN HIV/AIDS - Ahmad Amaludin; Raihan Nuur Hakim; Samsul Arifin (Universitas Lambung Mangkurat, 2026)
Human Immunodeficiency Virus (HIV) and Acquired Immune Deficiency Syndrome (AIDS) represent a global health crisis requiring long-term management. Understanding the factors influencing patient survival duration is crucial for effective clinical management. This study aims to model the survival rate of HIV/AIDS patients and determine dominant risk factors using Cox Proportional Hazard regression. This study utilized secondary data from the ACTG 175 clinical trial involving 2,139 patients. Parameter estimation was performed using the Maximum Partial Likelihood method, validated by the Schoenfeld residuals test. The results indicated that the Proportional Hazard assumption was met for all research variables. Simultaneously, the predictor variables significantly influenced the model. Partial testing identified Didanosine combination therapy (HR=0.715) and a history of drug use (HR=0.720) as protective factors. Conversely, clinical symptoms (HR=1.773), a history of Zidovudine use (HR=1.605), and low Karnofsky scores (HR=1.403) were identified as primary risk factors. Treatment factors and clinical conditions proved to have a more dominant influence on survival rates compared to demographic factors.